(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
In this article, inhibition of corrosion inhibitor synthesized on the basis of maleic anhydride, monoethanolamine and phosphoric acid was determined by effective gravimetric method. Fon-2(0,5 HCl+200 mg/l NaCl) medium and 70 0C temperature were studied.